Association of Body Mass Index With Colorectal Cancer Risk by Genome-Wide Variants. (3rd September 2020) - Campbell, Peter T; Lin, Yi; Bien, Stephanie A; Figueiredo, Jane C; Harrison, Tabitha A; Guinter, Mark A; Berndt, Sonja I; Brenner, Hermann; Chan, Andrew T; Chang-Claude, Jenny; Gallinger, Steven J; Gapstur, Susan M; et al.
Abstract: Background: Body mass index (BMI) is a complex phenotype that may interact with genetic variants to influence colorectal cancer risk. Methods: We tested multiplicative statistical interactions between BMI (per 5 kg/m 2 ) and approximately 2.7 million single nucleotide polymorphisms with colorectal cancer risk among 14 059 colorectal cancer case (53.2% women) and 14 416 control (53.8% women) participants. All analyses were stratified by sex a priori . Statistical methods included 2-step (ie, Cocktail method) and single-step (ie, case-control logistic regression and a joint 2-degree of freedom test) procedures. All statistical tests were two-sided. Results: Each 5 kg/m 2 increase in BMI was associated with higher risks of colorectal cancer, less so for women (odds ratio [OR] = 1.14, 95% confidence intervals [CI] = 1.11 to 1.18; P = 9.75 × 10 –17 ) than for men (OR = 1.26, 95% CI = 1.20 to 1.32; P = 2.13 × 10 –24 ). The 2-step Cocktail method identified an interaction for women, but not men, between BMI and a SMAD7 intronic variant at 18q21.1 (rs4939827; P observed = .0009; P threshold = .005). A joint 2-degree of freedom test was consistent with this finding for women (joint P = 2.43 × 10 –10 ). Each 5 kg/m 2 increase in BMI was more strongly associated with colorectal cancer risk for women with the rs4939827- CC genotype (OR = 1.24, 95% CI = 1.16 to 1.32; P = 2.60 × 10 –10 ) than for women with the CT (OR = 1.14, 95% CI = 1.09 to 1.19; P = 1.04 × 10 –8 ) or TT (OR = 1.07, 95% CI = 1.01 to 1.14; P = .02) genotypes. Conclusion: These results provide novel insights on a potential mechanism through which a SMAD7 variant, previously identified as a susceptibility locus for colorectal cancer, and BMI may influence colorectal cancer risk for women.